UPAYA GURU DALAM MENANAMKAN KARAKTER DISIPLIN PADA PESERTA DIDIK DI SD INPRES 3 TONDO - Oktariani, Ni Ketut; Putrayasa, I Wayan Budiagus; Narayanti, Putu Satya (STAH Dharma Sentana Sulawesi Tengah, 2024)
It is important to instill discipline in every person so that good character values ​​emerge. The importance of strengthening disciplined character is because currently there is a lot of deviant behavior occurring. This research aims to determine teachers' efforts to instill discipline character. The method used in this research is a qualitative descriptive method, primary data sources were obtained from 13 teachers consisting of 12 grade 1 principal teachers. Data collection techniques in this research used observation, interview and documentation techniques. The research results obtained show that teachers use several efforts to instill discipline character, namely example, rules, habituation, praise and punishment. Supporting factors in instilling students' disciplined character are supervision or control from the school principal, teachers being directly involved with students, awareness within students. Meanwhile, the inhibiting factors are the students' parents and the environment. The efforts made by teachers at SD Inpres 3 Tondo have achieved good results. With the efforts used by teachers in instilling a disciplined character in students, students can apply discipline to the environment and also to themselves. For example, students are orderly in their studies, come to school on time, and obey existing school rules, and respect teachers or respect their elders.